Don’t Wait Until It Escalates: Financial Assistance at Flinders University Student Association - Vanesa Duran Racero; Helen Laity (JANZSSA, 2015)
Financial hardship can be a major problem for university students, negatively impacting academic performance as well as general health and wellbeing. This article provides an overview of the on-campus financial services that the Flinders University Student Association provides to students. The range of support offered includes emergency financial assistance, interest-free loans, an annual grant scheme, financial literacy education, and financial counselling with an emphasis on debt management. Flinders University is the only South Australian University to employ a fully registered Financial Counsellor, who provides specialist services such as the ability to negotiate hardship variations for students under the National Consumer Credit Protection Act (2009). These services are independent and confidential, and are easier to access at Flinders than through the community sector. Timely assistance can help prevent individuals getting drawn further into a downward financial spiral, facilitating in turn continuous engagement with academic life.